Evaluation of structural vacancies for 1/1-Al–Re–Si approximant crystals by positron annihilation spectroscopy. Issue 2 (12th January 2018) - Yamada, K.; Suzuki, H.; Kitahata, H.; Matsushita, Y.; Nozawa, K.; Komori, F.; Yu, R. S.; Kobayashi, Y.; Ohdaira, T.; Oshima, N.; Suzuki, R.; Takagiwa, Y.; et al.
Abstract: The size of structural vacancies and structural vacancy density of 1/1-Al–Re–Si approximant crystals with different Re compositions were evaluated by positron annihilation lifetime and Doppler broadening measurements. Incident positrons were found to be trapped at the monovacancy-size open space surrounded by Al atoms. From a previous analysis using the maximum entropy method and Rietveld method, such an open space is shown to correspond to the centre of Al icosahedral clusters, which locates at the vertex and body centre. The structural vacancy density of non-metallic Al73 Re17 Si10 was larger than that of metallic Al73 Re15 Si12 . The observed difference in the structural vacancy density reflects that in bonding nature and may explain that in the physical properties of the two samples.